Edukasi Kesehatan Gigi dan Pemilihan Gigi Tiruan Lepasan pada Lansia di Posyandu Pojok - Desy Primalia Rizkiani (Jurnal Medika: Medika, 2026)
Oral health in the elderly significantly impacts their overall quality of life. One of the primary issues faced by the elderly is tooth loss, which affects chewing function and aesthetics. This study aimed to improve elderly knowledge on dental health and denture selection through a community service program at Posyandu Pojok. The community service program was conducted with 40 elderly participants at Posyandu Pojok. The approach included interactive lectures, discussions, demonstrations of denture installation, and free dental checkups for participants. This activity involved healthcare professionals, Posyandu cadres, students, and faculty members from the Faculty of Dentistry, Universitas Kadiri. The results showed a significant increase in participants' knowledge regarding denture care and the importance of maintaining oral hygiene. The free dental checkups also provided direct benefits by offering insights into participants' oral health conditions. This program positively contributed to enhancing the quality of life of the elderly with a better understanding of denture care. The study concludes that dental health education and denture care are crucial for improving the quality of life in the elderly.